PENGEMBANGAN HIGHER ORDER THINKING SKILL DALAM PENDIDIKAN ISLAM BERBASIS NEUROSAINS - Nanang Wahyudi; Ranu Suntoro; Awhinarto Awhinarto (At-Tajdid: Jurnal Ilmu Tarbiyah, 2020)
This study aims to determine the effectiveness of the application of HOTS in learning Islamic Neuroscience-based religious education. This research uses the Library Research method, the data analysis method uses the educational psychology approach, using the inductive thinking method supported by qualitative data. research results show HOTS in Neuroscience-based Islamic Religious Education can develop students' higher order thinking skills or High Order Thinking Skills (HOTS). This is evidenced from the planning stage, the implementation phase, and the evaluation phase containing HOTS indicators. The most dominant HOTS indicator is analyzing.